Chain‐growth condensation polymerization approach to synthesis of well‐defined polybenzoxazole: Importance of higher reactivity of 3‐amino‐4‐hydroxybenzoic acid ester compared to 4‐amino‐3‐hydroxybenzoic acid ester. Issue 12 (3rd April 2014) - Ohta, Yoshihiro; Niiyama, Tetsurou; Yokoyama, Akihiro; Yokozawa, Tsutomu
ABSTRACT Application of chain‐growth condensation polymerization (CGCP) to obtain well‐defined polybenzoxazole (PBO) was examined. CGCP of both phenyl 3‐{(2‐methoxyethoxy)methoxy (MEM‐oxy)}‐4‐(octylamino)benzoate (1b) (para‐substituted monomer) and phenyl 4‐MEM‐oxy‐3‐(octylamino)benzoate (3b) (meta‐substituted monomer) was examined in the presence of metal disilazide base and phenyl 4‐nitro‐ or methylbenzoate 2 as an initiator. Polymerization of the latter monomer, but not the former, afforded polymer with controlled molecular weight based on the feed ratio of monomer to initiator and with a narrow molecular weight distribution. Accordingly, monomer 3c, in which the octyl group on the amino nitrogen of 3b was replaced with a 4‐(octyloxy)benzyl (OOB) group, was polymerized in the presence of lithium 1, 1, 1, 3, 3, 3‐hexamethyldisilazide (LiHMDS), phenyl 4‐methylbenzoate (2b), and LiCl in THF at 0 °C to yield poly3c with well‐defined molecular weight (Mn = 4520–9080) and low polydispersity (Mw/Mn ≤ 1.11). Treatment of poly3c with trifluoroacetic acid simultaneously removed the MEM and OOB groups, affording poly(o‐hydroxyamide) (poly4) without scission of the amide linkages. Cyclodehydration of poly4 proceeded at 350 °C to yield PBO (poly5), which was insoluble in organic solvents and acids. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2014, 52, 1730–1736